2022
DOI: 10.3390/solar2040028
|View full text |Cite
|
Sign up to set email alerts
|

United States Solar Investment: A Feasibility Study of Solar Farms in Kentucky

Abstract: The United States is experiencing a large growth in the solar sector. The U.S. solar power capacity has grown from 0.34 Gigawatts (GW) in 2008 to an estimated 97.2 GW today. However, some states have had difficulty installing large scale solar farms due to concerns regarding geographic location, political climate, or economic factors. Kentucky (KY) is one of the states which is below the national average for solar energy production. However, KY contains a wealth of potential for these types of farms with decen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Consideration (4): Proximity to Load. Maryland's denser population compared to Kentucky led to a 20-mile radius containing at least 50,000 individuals being the criterion for considering a location [9]. Closeness to the load minimizes energy loss during transmission and reduces infrastructure needs.…”
Section: Proximity To Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…Consideration (4): Proximity to Load. Maryland's denser population compared to Kentucky led to a 20-mile radius containing at least 50,000 individuals being the criterion for considering a location [9]. Closeness to the load minimizes energy loss during transmission and reduces infrastructure needs.…”
Section: Proximity To Loadmentioning
confidence: 99%
“…Solar 2024, 4 247 Within the spectrum of renewable energy solutions, solar photovoltaic (PV) power has emerged as a frontrunner in addressing climate change and bolstering alternative energy adoption across the USA [7,9,10]. The International Renewable Energy Agency (IRENA) reported that in 2018, the levelized cost of electricity (LCOE) for utility-scale solar PV in the United States plummeted to just 3.7 cents per kilowatt-hour (kWh), underlining its economic viability and environmental benefits [11].…”
Section: Introductionmentioning
confidence: 99%